PENGARUH KOMBINASI INTENSITAS NAUNGAN DENGAN ZAT PENGATUR TUMBUH INDOLE BUTIRIC ACID (IBA), NAPHTHALENE ACETIC ACID (NAA), DAN VITAMIN B1 DALAM AKLIMATISASI PERTUMBUHAN BIBIT GAHARU (Aquilaria beccariana) - Mulyono, Daru (Jurnal Sains dan Teknologi Indonesia, 2012)
The objective of this research is to know the optimal formula of Indole Butiric Acid (IBA), Naphthalene Acetic Acid (NAA), Vitamine B1 and the combination with shading intensities to the acclimatization of Gaharu stump (Aquilaria beccariana). This research used Factorial Design with basic analysis of Complete Randomized Design in order to know theeffect of treatment. The research was carried out in Agroindustry and Biotechnology Laboratory, Ciampea, Bogor, from July to September 2007. The results of the research showed that after 8 weeks of treatment: (a). The combination of 55 % shading intensity with IBA 15 mg/l + NAA 10 mg/l + Vitamine B1 1 mg/l was the best formula for increasingheight of Gaharu stump 4.660 cm. (b). The combination of 55 % shading intensity with IBA 15 mg/l + NAA 30 mg/l + Vitamine B1 1 mg/l was the best formula for increasing sum of Gaharu leaf stump 12.337 leafs, (c). The combination of 55 % shading intensity with IBA 15 mg/l + NAA 40 mg/l + Vitamine B1 1 mg/l was the best formula for increasing sumof Gaharu root stump 3.783 roots, and (d). The combination of 55 % shading intensity with IBA 15 mg/l + NAA 40 mg/l + Vitamine B1 1 mg/l was the best formula for increasing length of Gaharu root stump 3.686 cm.